Level of lead contamination in the blood of Bali cattle associated with their age and geographical location - I Ketut Berata; Ni Nyoman Werdi Susari; I Wayan Sudira; Kadek Karang Agustina (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Berata IK, Susari NNW, Sudira IW, Agustina KK. 2021. Level of lead contamination in the blood of Bali cattle associated with their age and geographical location. Biodiversitas 22: 23-29. Lead contamination is increasingly common and endangers human as well as animal health. Cattle, which is a source of protein for humans, are very sensitive to lead exposure in a polluted environment. Therefore, this study aims to determine the level of lead contamination in the blood of Bali cattle related to their geographical location and age. A total of 300 cattle was drawn as the research sample, consisting of 150 each from the low and the highland. Each comprises of 50 young (<2 years old), 50 at puberty (2-3 years old), and 50 old cattle (>3 years old). The blood sample was taken from their jugular vein and collected in tubes containing ethylenediaminetetraacetic acid (EDTA) as anticoagulants. The lead content was measured using the atomic absorption spectrophotometer (AAS) method. The results showed average data for the lowlands, which include 0.430 ± 0.411 ppm, 0.792 ± 0.356 ppm, and 1.234 ± 0.533 ppm for young, puberty, and old, respectively. The highlands include 0.047 ± 0.074 ppm, 0.057 ± 0.061 ppm, and 0.089 ± 0.169 ppm for young, puberty, and old, respectively. Furthermore, the ANOVA showed a significantly higher (P<0.05) lead level in the blood of lowlands cattle than the highlands. We also found that in the lowlands, the lead level increased significantly (P<0.05) with the cattle's age, while the highlands show no difference. Based on the results, it is concluded that cattle in the lowlands are more exposed to lead than cattle in the highlands. Also, the increase in the blood lead level associated with age occurs only in cattle of the lowlands.